Populations in Crisis: Migration Plans and Determinants Among Medical Students During the COVID-19 Pandemic - Anastasiou, Evgenia (Migration Letters, 2022)
The recent pandemic has had a considerable impact on sociodemographic development and generated a new interest in human mobility. The current study aims to examine the effects of sociodemographic development and the push-pull of brain drain as well as COVID-19-related factors on Greek medical students’ intentions to emigrate. A total of 531 undergraduate medical students completed an online survey during the second transmission wave of the pandemic in Greece (from October to December 2020). The results showed that many students were considering emigrating after their graduation. A multiple regression analysis revealed that males and younger students presented a higher likelihood of emigration. The low absorption rate of physicians in Greece, lack of career prospects, low earnings, general frustration with the governance, and the cultural mindset of the Greek population were predictors of the medical brain drain. In many cases, COVID-19 strengthened the resolve to emigrate as most medical students did not consider the pandemic to be a deterrent to seeking better luck abroad.